Tax expenditures in local taxes - an effective instrument of local tax policy? The example of Poland - Paweł Felis; Grzegorz Gołębiowski (Contemporary Economics, 2021)
This study examines the size and diversity of tax expenditures (TEs) by gminas (municipalities) in Poland between 2007 and 2019. Consequences of gminas' taxing power and the reduction of revenues resulting from statutory tax preferences were taken into account. To analyze the data, we used: scatter graphs (showing the relationship between two selected variables) and plot graphs (showing the course of the values of the studied variables over time, to show the dynamics of the phenomena). The scatter graphs showed, sometimes strong, linear correlative relationships. No clear curvilinear relationships were found, therefore we applied Pearson correlation. Gminas used TEs to a small but also highly variable extent. The factors determining their use involved: the type and potential of the gmina; the type of local tax. The research hypothesis was partially positively verified. The increase in the incremental % of TEs' share in tax revenue has a positive impact on the incremental trend of revenue growth in the following year. The use of TEs in real estate and vehicle taxes may have strengthened the revenue potential of some gminas in the consecutive years.
Keywords: E62; H71; H72; R51; 330; Tax expenditures; local authority tax policy; local taxes